Tingenone, a Pentacyclic Triterpene, Induces Peripheral Antinociception Due to Opioidergic Activation - Veloso, Clarice de Carvalho; Rodrigues, Vanessa Gregório; Ferreira, Renata Cristina Mendes; Duarte, Lucienir Pains; Klein, Andre; Duarte, Igor Dimitri; Romero, Thiago Roberto Lima; Perez, Andrea de Castro (Planta Medica, 2014)
Plants belonging to the genus Maytenus are routinely used in folk medicine for the treatment of pain diseases. Our previous phytochemical study of the roots of Maytenus imbricata resulted in the isolation and characterization of tingenone, a pentacyclic triterpene. Natural triterpenoids are of growing interest because they have several biological activities, including analgesic properties. The present study assessed the involvement of the opiodergic pathway in the tingenone-induced antinociceptive effect against hyperalgesia induced by prostaglandin E2 (2 µg) in the peripheral pathway. We evaluated the effect of several antagonists to opioid receptors using the mouse paw pressure test. Tingenone administered into the right hind paw induced a local antinociceptive effect that was antagonized by naloxone, a nonselective antagonist to opioid receptors. Clocinnamox, naltrindole, and nor-binaltorphimine are selective antagonists to µ, δ, and κ receptors, respectively, which reverted the peripheral antinociception induced by tingenone. Bestatine acts as an inhibitor of aminopeptidase, an enzyme that degrades endogenous opioid peptides, and was shown to intensify the antinociceptive effect of tingenone. The results suggest that the opioidergic system participates in the peripheral antinociception induced by tingenone.
Keywords: Maytenus imbricata; Celastraceae; tingenone; pentacyclic triterpene; opioid receptors; peripheral antinociception